Giant and Linear Piezo‐Phototronic Response in Layered GaSe Nanosheets. (19th February 2018) - Jia, Tanhua; Fuh, Huei‐Ru; Chen, Dengyun; Abid, Mohamed; Abid, Mourad; Zhang, Duan; Sarker, Anas B.; Cho, Jiung; Choi, Miri; Chun, Byong Sun; Xu, Hongjun; Ó Coileáin, Cormac; et al.
Abstract: Piezo‐phototronic devices, where optoelectrical properties are directly influenced by mechanical stimuli, are highly desirable for applications in wearable devices and human–machine interfaces. Here, the piezoelectric and piezo‐phototronic properties of GaSe nanosheets, a layered metal‐monochalcogenide III–VI semiconductor with interesting piezoelectric, optical excitation, and semiconducting properties are investigated. A giant piezo‐phototronic response in GaSe is demonstrated for the first time. The out‐of‐plane local field due to band gap modulation drives the electrons (holes) to move toward the outer (inner) surface of wrinkles, which enhances electron–hole pair generation and the related photocurrent. Moreover, manual bending of GaSe reliably enhances the photocurrent by more than a factor of 50 at room temperature. This giant and linear piezo‐phototronic response combined with excellent stretchability suggests that GaSe is a valuable material for flexible optoelectronic‐mechanical applications. Abstract : GaSe is a layered metal‐monochalcogenide III–VI semiconductor with interesting piezoelectric, optical excitation and semiconducting properties. A giant and linear piezo‐phototronic response is demonstrated in GaSe nanosheets. Manual bending reliably enhances the photocurrent more than a factor of 50, at room temperature. This robust piezo‐phototronic response combined with excellent stretchability suggests GaSe is a valuable material for flexible optoelectronic‐mechanical applications.